The Effects of Age, Sex and Education on HVLT-R Performance Across the Lifespan: Data from the NEUROAGE Cohort - Nikolaou, Flora; Michaelides, Michalis; Prokopiou, Juliana; Metaxas, George; Constantinidou, Fofi (Psychology: the Journal of the Hellenic Psychological Society, 2024)
The study investigates the impact of age, education, and sex on memory within a diverse cohort of participants spanning the adult lifespan, utilizing the G-HVLT-R. A total of 1,055 Greek Cypriot individuals, both males and females aged 18 to 80, were recruited from the NEUROAGE longitudinal project. Participants underwent a comprehensive battery of neuropsychological tests, including the G-HVLT-R for assessing total learning and delayed recall, alongside the Logical Memory test measuring delayed recall performance in story recall. Significant performance disparities emerged between Forms 1 and 2 and Forms 1 and 3 of the G-HVLT-R. Regression analyses revealed age as the predominant predictor, with the highest coefficients, followed by education and sex. Notably, the G-HVLT-R demonstrated robust concurrent validity, evidenced by high correlation coefficients with Logical Memory delayed recall tasks. The findings underscore age as the primary determinant of performance, while also emphasizing the influence of education and sex across the lifespan. Consequently, establishing norms that account for demographic characteristics is imperative for refining the precision of neuropsychological assessment, particularly among those with lower education levels and in older age groups. This information enhances accurate clinical assessment across diverse populations and aids in identifying individuals necessitating specific treatment interventions.